THE USE OF INNOVATIVE EDUCATIONAL TECHNOLOGIES IN THE TRAINING OF PEDAGOGICAL EDUCATORS - Burkhanov Zavqiddin (Web of Journals Publishing, 2024)
This article looks at the issues of using innovative technologies for training future pedagogues using innovative educational technologies.
Keywords: Education, education, innovation, technology, educational technologies.